2022
DOI: 10.19109/ejpp.v9i1.10901
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Strategies in Teaching Reading Comprehension through E-learning Platform during the Pandemic

Abstract: This study was aimed to explore EFL teachers' strategies in teaching reading comprehension through an e-learning platform at one public senior high school in Jambi. This study employed a qualitative research design which was a case study. The study utilized two data collection techniques: observation and interview. Two teachers of English were involved in this study. All of the data were analyzed using four significant stages of analysis: coding, data reduction, data display and concluding. The frequency of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In line with our study, the results of Indah et al (2018) showed that using skimming as a reading technique by nursing students was associated with a better understanding of the material (34). In fact, skimming helps students to predict the purpose and the main idea of the text they are studying (35). Some of the students participating in our study stated that one of their strategies for a better and deeper understanding of the course material was playing the role of a professor.…”
Section: Self-directed Learning Strategiessupporting
confidence: 85%
“…In line with our study, the results of Indah et al (2018) showed that using skimming as a reading technique by nursing students was associated with a better understanding of the material (34). In fact, skimming helps students to predict the purpose and the main idea of the text they are studying (35). Some of the students participating in our study stated that one of their strategies for a better and deeper understanding of the course material was playing the role of a professor.…”
Section: Self-directed Learning Strategiessupporting
confidence: 85%
“… Skimming - using skimming as a reading technique by nursing students is associated with a better understanding of the material [ 42 ]. - skimming helps students to predict the purpose and the main idea of the text they are studying [ 43 ]. Individual role playing - Role-playing is a fun and stimulating strategy for students [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…- skimming helps students to predict the purpose and the main idea of the text they are studying [ 43 ].…”
Section: Discussionmentioning
confidence: 99%